TANTANGAN PENERAPAN BLOCKCHAIN DALAM SISTEM E-VOTING DI INDONESIA - Fitra Sugiarto; Reymond Agung Hutabarat; A. Reza Ardika Yasin; Aditya Wicaksono Rumbekwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The dynamic and rapid development of technology is an alternative for daily life activities as an effective and efficient tool. One of the technological innovations that has received a lot of attention is blockchain technology. This research uses a literature review approach. The data used in this research comes from various scientific publications, including journal articles, conference proceedings, research reports, and books. The literature search was conducted through reputable academic databases such as IEEE Xplore, Google Scholar, Scopus, and ScienceDirect. These sources were chosen for their credibility and extensive global coverage, particularly in the field of information and communication technology. The main focus is on publications that discuss the application of blockchain in e-voting systems, both in terms of advantages, challenges, and potential implementation in various countries. The results reveal that the application of blockchain technology in e-voting systems in Indonesia faces various challenges, especially related to information and communication technology (ICT) infrastructure, regulations, and public acceptance. In terms of infrastructure, the government should accelerate the development of network infrastructure, including expanding 4G/5G networks and utilizing complementary technologies such as edge computing and communication satellites. Second, Indonesia needs to adapt a regulatory framework that supports the use of blockchain in elections, with reference to cryptographic principles to protect data and ensure election integrity. Third, public acceptance of blockchain technology in e-voting requires an approach that takes into account psychological and social aspects.